Evaluation of anti-nNav1.5 antibodies as potential therapeutic agent in suppressing breast cancer invasion and metastasis - Sharudin, Nur Aishah (2022)
Advanced-stage breast cancer has the poorest survival rates and contributes to 90% of cancer mortality, primarily due to limited molecular targets and treatment options. In this study, a novel target for metastatic breast cancer, a splice variant of Nav1.5 named ‘neonatal’ Nav1.5 (nNav1.5), a member of the family of voltage-gated sodium channels (VGSCs), was evaluated. nNav1.5 has a strong association with breast cancer metastatic potential through its role in cell migration, invasion in vitro, and metastasis in vivo. Monoclonal (mAb-nNav1.5) and polyclonal antibodies based on purified IgG (pAb-nNav1.5) or whole serum against nNav1.5 were obtained, which were evaluated as potential immunotherapeutic agents, investigating their effects on the invasion of breast cancer cells in vitro and their anti-tumoral and anti-metastatic effects in an animal model. This present study is aimed to produce monoclonal and polyclonal antibodies against a specific epitope of nNav1.5 and characterize their reactivity against nNav1.5 expressing breast cancer cells. Next, to investigate the therapeutic effects and anti-metastatic potential of these agents on the invasion of the 3D-spheroids culture of breast cancer cell lines and to evaluate the therapeutic effect of the mAb-nNav1.5 and pAb-nNav1.5 administration in a model of tumour induction with 4T1 cell line in BALB/c female mice. Findings demonstrated that the immunoreactivity of mAb-nNav1.5, pAb-nNav1.5 and serum of immunized animals against the specific nNav1.5 epitope, was confirmed in cells and lysates of nNav1.5 expressing cells, MDA-MB-231 and 4T1 cells based on ELISA, Western blotting and immunocytochemistry. Moreover, mAb-nNav1.5, pAb-nNav1.5, and nNav1.5 polyclonal serum suppressed the invasion of MDA-MB-231-3D and 4T1 3D-spheroids (30-58%, 30-50%, and 10-55%, respectively) followed by reduced nNav1.5 gene (3-5 folds) and protein expression, similar to tetrodotoxin (TTX), a potent channel blocker which was used as control drug. Finally, treatment with mAb-nNav1.5 and pAbnNav1.5 resulted in reduced tumour burden of 4T1-induced mammary tumour in BALB/c female mice, which maintained higher body weight, smaller tumour size, and absence of inflammation/macro metastatic lesions in organs (lungs, spleen, intestines, and liver) as compared to control group (PBS treated). Subsequent gene expression analysis revealed downregulation of nNav1.5 expression in the animals’ primary tumour tissues. Collectively, this study confirms the novelty of targeting nNav1.5 in suppressing breast cancer invasion and prevention of metastasis but importantly, humanized versions of mAb-nNav1.5 may represent useful passive immunotherapeutic agents to target nNav1.5 in breast cancer.